Improvement of hydroponic medium to promote rooting and control of root gall development on black pepper cutting - Babirye, Khadijah (2021)
Stem cutting is the common planting material for black pepper (Piper nigrum L.) farmers, but soil propagation renders both the planted material and new developing plant susceptible to soil-borne parasites such as root knot nematodes (RKN). Hydroponic cultivation technique thus offers a platform for manipulating root growth conditions, commencement of plant production under zero risk of soil parasites, hence a more extensive root system with improved strength to resist soil pathogens. The present research thus aimed to; (i) establish the most suitable nutrient composition and stem cuttings for promoting root-stock growth of black pepper (P. nigrum cv. ‘Kuching’) plants through hydroponic cultivation (ii) assess the effect of potassium silicate and salicylic acid on RKN infestation in black pepper plants (iii) evaluate the oxidative stress by assessing the production of superoxide anion (O2•-) and hydrogen peroxide (H2O2) in black pepper plants after inoculation of the plant rhizosphere with RKN and identifying cellular sites of O2•- plus H2O2 accumulation in leaves of inoculated black pepper plants. A total of 210 stem cuttings were hydroponically planted in uniformly-sized growing trays and arranged in a completely randomized design in the laboratory. Seven nutrient solutions (NS) were investigated, with each NS containing an equal number of stem cuttings with adventitious roots (R) and stem cuttings without any root (U) at the time of planting. Plant response data was collected for a total period of 4 weeks. Hoagland solution supplemented with 0.005 mM potassium silicate solution (T4) and Hoagland solution supplemented with 2 mM salicylic acid solution (T6) showed faster root initiation whereas T1 (Hoagland solution only) produced the highest increment in root length of plants. The least suitable nutrient composition was T5 [T4 + 6 mL of 1 M Ca (NO3)2.4H2O solution]. Roots for plants whose stem cuttings did not have any root at the time of planting (U) increased in root length faster than plants whose stem cuttings had some adventitious roots at the time of planting (R). Hydroponic plants in T1, T4 and T6 were transplanted into the soil medium and introduced to greenhouse conditions while maintaining the NS for each plant. After acclimatization to both soil and greenhouse conditions, plants were inoculated with RKN. The number of P. nigrum cv. ‘Kuching’ plants exhibiting foliar symptoms of RKN infection followed the order T1 > T6 > T4 > uninoculated plants. Aerial growth of RKN- inoculated plants was highest in plants irrigated with T4, followed by T6. Total number of root galls followed the order T1 > T6 > T4. Present results indicate that supplementation of the NS with potassium silicate (T4) provided the highest plant resistance against the influence of RKN. This finding was additionally reflected in the oxidative stress experiment which revealed least O2•- and H2O2 production in leaves of RKN-inoculated plants irrigated with T4 compared to plants irrigated with T1 and T6. Results of this study could be used by black pepper farmers for inducing RKN resistance of the plant through soil nutritional amendment with potassium silicate.